Flow-splitting algorithm of MPLS single label based on programmable router - Lai-quan HAN; Jin-kuan WANG; Xing-wei WANG (Tongxin xuebao)
To increase the QoS (quality of service) of data transmission, a novel flow-splitting algorithm, multipathMPLS, was proposed, which combined three technologies of MPLS (multi protocol label switching), concurrent multi-path and programmable router. MultipathMPLS implementes the flow-splitting transmission for the same FEC (forwarding equivalence class). Via the network simulation tool (NS2), this algorithm can obtain the high forwarding performance of MPLS, high throughput of concurrent multi-path and flexible configuration of programmable router.